Lynch Syndrome Germline Mutations in Breast Cancer: Next Generation Sequencing Case-Control Study of 1,263 Participants - Nikitin, Aleksey G.; Chudakova, Daria A.; Enikeev, Rafael F.; Sakaeva, Dina; Druzhkov, Maxim; Shigapova, Leyla H.; Brovkina, Olga I.; Shagimardanova, Elena I.; Gusev, Oleg A.; Gordiev, Marat G. (Frontiers in Oncology, 2020)
Genome instability – the increased tendency of acquiring mutations in the genome and ability of a cell to tolerate high mutation burden - is one of the drivers of cancer. Genome instability results from many causes including defects in DNA repair systems. Previously, it has been shown that germline pathogenic mutations in DNA Mismatch Repair (MMR) pathway cause cancer-predisposing Lynch Syndrome. We proposed that Lynch Syndrome-related germline mutations (LS-mutations) are associated with breast cancer (BC). In this study, we performed Targeted Next-Generation Sequencing of MMR pathway genes MLH1, MSH2, MSH6, EPCAM, and PMS2 in a cohort of 711 patients with hereditary BC, 60 patients with sporadic BC, and 492 healthy donors. Sixty-nine patients (9.7%) with hereditary BC harboured at least one germline mutation in the MMR pathway genes, of them thirty-two patients (4.5%) harboured mutations in MMR pathway genes which we define as pathogenic or likely pathogenic, and of them twenty-six patients (3.6%) did not have any pathogenic mutations in DDR pathway genes, compared to two mutations in MMR pathway genes (0.4%) detected in a group of 492 healthy donors (p = 0.00013, OR = 8.9 (CI 95% 2.2 - 78.4)). Our study demonstrates that LS-mutations are present in patients with hereditary BC more frequently than in healthy donors, and that there is an association of hereditary BC and mutations c.1321G>A in MLH1, c.260C>G and c.2178G>C in MSH2, c.3217C>T in MSH6, c.1268C>G and c.86G>C in PMS2 genes. This finding provides a rationale for including pathogenic LS-mutations into genetic counselling tests for patients with hereditary BC.